KEPUTUSAN PEMBELIAN PADA MIXUE DI KECAMATAN SUMBAWA MELALUI PERSEPSI HARGA, LOKASI DAN KUALITAS PRODUK - Dewi, Yulia Puspita; Ananda, Nova Adhitya (Jurnal Nusa Manajemen, 2025)
This study aims to test the Purchase Decision at Mixue in Sumbawa District Can Be Seen From the Perception of Price, Location and Product Quality. This study uses a quantitative method with a descriptive approach. Data collection techniques using questionnaires. The sample in this study amounted to 100 respondents through the Paul Leedy formula and the Non Probability Sampling technique with the Purposive Sampling approach. Three Boxs Method data analysis technique. The results of the study indicate that the Purchase Decision at Mixue in Sumbawa District can be seen from the Perception of Price because the products offered by Miixue are also relatively cheap so that consumers will make repeat purchases or recommend to their relatives. Based on the results of this study, it can be concluded that the Purchase Decision at Mixue in Sumbawa District can be seen from the Location. This is because the location of Mixue is fairly strategic because it is in the middle of the city, precisely in a shopping center that allows consumers to visit at any time. Based on the results of this study, the Purchase Decision at Mixue in Sumbawa District can be seen from Product Quality. This is because the quality provided by Mixue is in accordance with the delicious taste that will make consumers make repeat purchases on the product.